2013
DOI: 10.1603/ec12458
|View full text |Cite
|
Sign up to set email alerts
|

EAG Responses of <I>Apis cerana</I> to Floral Compounds of a Biodiesel Plant, <I>Jatropha curcas</I> (Euphorbiaceae)

Abstract: The Eastern honey bee, [Apis cerana (F.)], is an important and common pollinator for an important biodiesel tree, [Jatropha curcas (L.)]. To understand sensitivity of A. cerana to different floral compounds, we quantified volatile floral compounds of J. curcas, then determined electroantennogram (EAG) responses of A. cerana to 11 compounds each at five doses (0.4, 4, 40, 400, and 4,000 microg) of six most active floral compounds. Our results demonstrated that floral compounds of J. curcas differ in variety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
2
1
Order By: Relevance
“…Ukeh et al showed that a synthetic blend of hexanal, octanal, and (E)-2-heptanal identified from maize seed volatiles was significantly attractive to Sitophilus zeamais (Coleoptera: Curculionidae) . Similar studies have been reported on various insect species, for example, Triatoma infestans (Hemiptera: Reduviidae), Dinoderus minutus (Coleoptera: Bostrichidae), and Apis cerana (Hymenoptera: Apidae). Our results are consistent with these findings, showing that aldehydes are attractive to insect target insects. Uechi et al showed that hexanal was not attractive to P.…”
Section: Discussioncontrasting
confidence: 99%
“…Ukeh et al showed that a synthetic blend of hexanal, octanal, and (E)-2-heptanal identified from maize seed volatiles was significantly attractive to Sitophilus zeamais (Coleoptera: Curculionidae) . Similar studies have been reported on various insect species, for example, Triatoma infestans (Hemiptera: Reduviidae), Dinoderus minutus (Coleoptera: Bostrichidae), and Apis cerana (Hymenoptera: Apidae). Our results are consistent with these findings, showing that aldehydes are attractive to insect target insects. Uechi et al showed that hexanal was not attractive to P.…”
Section: Discussioncontrasting
confidence: 99%
“…Generally, flowering plants attract pollinators by promising reward, floral mimicry or sexual deceptive, and the well‐developed sensory bias response for distinct volatiles is crucial (Raguso, 2008; Schiestl, 2015). Electroantennogram (EAG) is an electrophysiological technique used to detect insect responses to volatile compounds, and it has been experimentally confirmed that a variety of insects exhibit significant electrophysiological responses to linalool, which is an important elicitor of insect pollination behavior (Raguso et al, 1996; Johnson et al, 2007; Luo et al, 2013; Braunschmid et al, 2017; Lukas et al, 2019).…”
Section: The Role Of Linalool In the Interaction Of Plants With Polli...mentioning
confidence: 99%
“…In many cases, researchers have found that flowers that release linalool also attract bees, like Paullinia cupana , Silene otitis , and Medicago sativa (Henning et al, 1992; Dötterl et al, 2012; Krug et al, 2018; Table 2). The electrophysiological response test of insect antennae is often used to detect whether the insect is sensitive to a certain chemical compound, which has been employed to confirm that multiple bees like Lasioglossum , Andrena , Nomada , and Apis cerana are all sensitive to linalool (Luo et al, 2013; Braunschmid et al, 2017; Lukas et al, 2019). However, it is worth noting that whether a higher concentration of linalool exhibits stronger attraction to insects.…”
Section: The Role Of Linalool In the Interaction Of Plants With Polli...mentioning
confidence: 99%